2018
DOI: 10.1007/s11071-018-4383-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear mechanics of flexible cables in space robotic arms subject to complex physical environment

Abstract: A nonlinear model of a special cable in space robotic arms is developed in space environment. The mechanic effects of control cables in powerful robots can often be neglected. However, in complex space multi-physics environments, involving ultra-low temperature, radiation, and other extreme conditions of outer space, the externally mounted cables (protected by shielding layers) can induce strong nonlinear interference to robot arms; and this can induce further small-range slow rotations or oscillations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The analysis of deflection deformation of connecting rod is relatively simple, which can be simplified into a deformation model of cantilever beam under uniform load. The moment effect of self weight of manipulator on the flexible joint always exists [7]. The corresponding flexibility error is coupled with the geometric error, but it cannot be obtained by changing the posture.…”
Section: Flexibility Error Of Manipulatormentioning
confidence: 99%
“…The analysis of deflection deformation of connecting rod is relatively simple, which can be simplified into a deformation model of cantilever beam under uniform load. The moment effect of self weight of manipulator on the flexible joint always exists [7]. The corresponding flexibility error is coupled with the geometric error, but it cannot be obtained by changing the posture.…”
Section: Flexibility Error Of Manipulatormentioning
confidence: 99%
“…In 2006, Feyrer [12] found that the local deformation of a single steel wire is affected by the fatigue and damage behavior of steel wire rope. For marine flexible pipe/cables, Kirchhoff's nonlinear mechanical model was developed, and the theoretical accuracy was verified experimentally by Liu [13]. Some theoretical models are proposed to calculate the local pressure, radial force and contact force between the cable armor layer [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…To better solve the first problem, we hope to deeply study the principle of dynamic coupling in the system, and then quantify the degree of coupling, so as to provide a basis for effective control methods. As for the second point, we use a control way based on a velocity closed loop to take a linearization analysis for the nonlinear problem (Liu et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%